Market scenarios and mixed analysis approach. Relationship between semiotic and retail marketing methods. Communication of the performance indicators of a store - Barone, Tiziana (E|C, 2020)
In this paper, starting from Floch’s research and comparing the semiotic methodology, that aims to produce the semantic representation of an object of analysis, and the mixed (qualitative-quantitative) method to the retail marketing prerogative, an interpretative analysis is proposed and the reading effect of the data processed in Company Performance Indices (KPI). The aim of the research is to give a new perspective to reading and communicate the indexes, to build a business strategy.